How does academic self-efficacy influence learning anxiety and academic burnout in Chinese characters learning among international students in China? - Lin, Yang (Frontiers in Psychology, 2025)
BackgroundThe interplay between learning self-efficacy, anxiety, and burnout has been extensively documented in English as a Second Language (ESL) education. However, Chinese character learning—a uniquely complex task involving visual–spatial processing, stroke order mastery, and radical decomposition—presents distinct cognitive and affective challenges. The dynamics of self-efficacy, anxiety, and burnout in Chinese character acquisition remain under-explored, creating a critical gap in understanding how these constructs operate in non-alphabetic language contexts.ObjectiveThe purpose of this study was to investigate how learning anxiety (LA) affects academic burnout (AB) and explores the role of academic self-efficacy (ASE) in the relationship between the two.MethodsA study of 537 international students (50.4% males, mean age = 20.96 years, SD = 1.36) was conducted using the Academic Self-Efficacy Scale (ASES), Foreign Language Learning Anxiety Scale (FLLAS), Academic Burnout Scale (ABS).Results① LA was significantly and positively correlated with AB, and significantly and negatively correlated with ASE. ② ASE mediated the relationship between LA and AB. ③ Grade level, sleep quality, and parental education level have a significant effect on ASE, LA and AB; and ④ Extroversion has a significant effect on ASE, but not on LA and AB.ConclusionThe chain mediation model validated by this study provides valuable insights into the effects of international students’ learning anxiety (LA) on academic burnout (AB) in China, alongside practical implications for preventing and intervening in LA and AB among other current students.